2017
DOI: 10.1017/s1047951117001536
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-induced cardiotoxicity in patients with paediatric bone sarcoma and soft tissue sarcoma

Abstract: In our population, the cumulative incidence of cardiotoxicity is comparable to rates in the literature. This underlines the need for primary prevention and lifelong cardiac toxicity surveillance programmes in long-term childhood cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
4
19
0
1
Order By: Relevance
“…Different chemotherapy agents cause cardiotoxicity through a wide variety of mechanisms, causing not only cardiomyopathy but also hypercoagulable states, arrhythmia, and inflammation [4]. Anthracyclines such as daunorubicin, doxorubicin, and mitoxantrone are the most well-studied and cause dose-dependent cardiomyopathy and congestive heart failure [1, 58]. These agents work against cancer by cross-linking topoisomerase IIα to DNA and directly intercalating with DNA, resulting in DNA damage, apoptosis, mitochondrial injury, increased reactive oxygen species [6], and programmed cell death [9].…”
Section: Chemotherapeutic Agents That Cause Cardiotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Different chemotherapy agents cause cardiotoxicity through a wide variety of mechanisms, causing not only cardiomyopathy but also hypercoagulable states, arrhythmia, and inflammation [4]. Anthracyclines such as daunorubicin, doxorubicin, and mitoxantrone are the most well-studied and cause dose-dependent cardiomyopathy and congestive heart failure [1, 58]. These agents work against cancer by cross-linking topoisomerase IIα to DNA and directly intercalating with DNA, resulting in DNA damage, apoptosis, mitochondrial injury, increased reactive oxygen species [6], and programmed cell death [9].…”
Section: Chemotherapeutic Agents That Cause Cardiotoxicitymentioning
confidence: 99%
“…Despite recent advances in cancer treatment, cardiotoxicity can result from traditional chemotherapy agents such as anthracyclines, as well as newer targeted therapies, such as trastuzumab, leading to significant morbidity and mortality [14]. Radiation therapy alone and in combination with chemotherapy can also contribute to cardiotoxicity [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important for risk factors to be detected, which include: some polymorphisms, obesity, arterial hypertension, age younger than four years, female gender, metabolic syndrome, radiotherapy higher than 5 Gy, monoclonal antibodies, hematopoietic cell transplantation, mitoxantrone, 5-fluoroacil, alkylating agents such as cyclophosphamide, cisplatin, biological agents such as trastuzumab and rituximab, and tyrosine kinase inhibitors such as imatinib, sunitinib and dazatinib [8][9][10][11] . The factor that entails the highest risk in statistical analyses is anthracycline cumulative dose ≥ 300 mg/m 2 , with an incidence of up to 14.6%.…”
Section: Introductionmentioning
confidence: 99%
“…In general, treatment for lymphoma involves chemotherapy alone or in combination with radiation, stem cell transplantation, or biologic therapies . The long‐term cardio‐toxic effects of these treatments, especially chemotherapy regimens utilizing anthracyclines and radiation therapy, have become more apparent in cancer survivors over the past decade . We previously conducted a meta‐analysis and found that the number of deaths due to CVDs within HL and NHL survivors were 7.31 (95% CI, 5.29‐10.10) and 5.35 (95% CI, 2.55‐11.24) times greater than the general population, respectively .…”
Section: Introductionmentioning
confidence: 99%